2019
DOI: 10.1186/s12889-019-6590-y
|View full text |Cite
|
Sign up to set email alerts
|

Dental care utilization: examining the associations between health services deficits and not having a dental visit in past 12 months

Abstract: Background: A growing literature supports the contention that closing the divide between dental and medical care can improve access to and coordination of patient care. Health service deficits (HSDs) entail: no routine medical exam, no personal healthcare provider (HCP), no health insurance, and/or delaying medical care because of cost all within the last 12 months. Examining the associations between HSDs and dental care utilization could inform strategies and interventions aimed at narrowing the gap between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 55 publications
9
66
0
3
Order By: Relevance
“…Women were less likely to visit dentist in period longer than 12 months compared to men (OR=0.70). According to the literature women more regularly visit a dentist than men 20 , which also confirm the survey results by developed countries such as Germany and United States 21,22 . In a cross-sectional study in Turkey 23 , women had more visits to the dentist compared to men during a previous 12-month period.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Women were less likely to visit dentist in period longer than 12 months compared to men (OR=0.70). According to the literature women more regularly visit a dentist than men 20 , which also confirm the survey results by developed countries such as Germany and United States 21,22 . In a cross-sectional study in Turkey 23 , women had more visits to the dentist compared to men during a previous 12-month period.…”
Section: Discussionsupporting
confidence: 81%
“…In regards to the place of residence in our research, we note that respondents who live in rural area tend to visit a dentist once in 12 months period or longer more frequently in comparison to residents of the city. This trend has been confirmed by a study conducted in the United States on the population age 18 9 years and older, where rural residency was shown as an independent factor associated with lower dental care utilization 22 . Research showed that the population of the rural area is most likely to visit a dentist only when they experience acute pain 27,28 .…”
Section: Discussionmentioning
confidence: 53%
“…One limitation of the present study is that it does not assess the oral and general health of the subjects (dental caries indices, complete or partial edentulism, periodontal status, presence of general diseases, and so on). Another limit is the social desirability bias meaning that a patient think it is a must to visit a medical or dental office at every six month or one a year, they can choose to answer desirably (to report a regular healthcare visit) even if this is not true (4).…”
Section: Discussionmentioning
confidence: 99%
“…For clinicians, there is a need to deliver comprehensive medical care in a patient-centered approach health, prioritizing the interventions towards increasing regular dental and general services use, considering the impact of health on individuals' lives (2,3). Regular medical care provides the opportunity for improved health outcomes, preventive treatments and early detection of dental and general diseases (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation